The traditional Chinese medicine and non-small cell lung cancer: from a gut microbiome perspective - Wang, Xuelin; Hou, Liming; Cui, Meng; Liu, Junnan; Wang, Mengzhou; Xie, Jianwu (Frontiers in Cellular and Infection Microbiology, 2023)
Non-small cell lung cancer (NSCLC) is one of the major diseases affecting human health at present, and intestinal flora is the focus of current research. There is a correlation between intestinal flora imbalance and lung cancer, but the specific mechanism is not clear. Based on the “lung and large intestine being interior-exteriorly related” and the “lung-intestinal axis”theory. This paper, through the theoretical comparison of Chinese and western medicine, summarizes and analyzes the regulation of intestinal flora of NSCLC by active ingredients of traditional Chinese medicine and Chinese herbal compounds and their intervention effects, which is conducive to providing new strategies and ideas for clinical prevention and treatment of NSCLC.